PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BAGI KELOMPOK USAHA EKONOMI PRODUKSI NGUDI LESTARI BINAAN KANTOR DESA KEMBANG KAPANEWON NANGGULAN KABUPATEN KULON PROGO YOGYAKARTA - Rini Susiani; Paulus Sugianto Yusuf; Supriyanto Ilyas; Ingrid Larasati Agustina; Tria Apriliana (Jurnal Abdimas Bina Bangsa, 2024)
Widyatama University in collaboration with the Kembang Kapanewon Nanggulan Village Office, Kulon Progo Regency, Yogyakarta, provided Training on Preparing Simple Financial Reports for the Ngudi Lestari Production Economics Business Group to gain knowledge and skills so that they can provide guidance and assistance to the Production Economics Business Group under the supervision of the Village Office. The right suggestions and solutions will help solve the problems faced by business people, who generally have low education and insufficient expertise